KELUARGA MERUPAKAN PENDIDIKAN AWAL BAGI ANAK - Riana Friska Siahaan (JURNAL KELUARGA SEHAT SEJAHTERA, 2013)
ABSTRACT The family is the cradle where children first see the light of life , so anything that was poured in a family will leave a deep impression of the character , thoughts and attitudes and behavior of children . Because the purpose of building a family life is to be able to give birth to a new generation as the successor struggles parents . For that parents have a responsibility and obligation in their children's education . One of the roles of parents towards their children's education success is to pay attention, especially attention on their learning activities at home . Attention parents have a huge psychological impact on children's learning activities . With the attention of the parents , the child will be more active and   eager to learn because he knew that it was not himself who is eager to move forward , but the parents too. Because the merits of the achievements of children would give him influence in the development of further education . The totality of the attitude of parents in caring for all children undergoing routine activities as a student is required so that the child easily in transferring knowledge during their learning process , in addition it also so that he can achieve maximum learning . Attention parents may be providing guidance and advice , supervision of learning , motivation and reward , learning and fulfillment facilities. Kata Kunci : Keluarga, pendidikan awal.